International stock–bond correlations in a simple affine asset pricing model - d’Addona, Stefano; Kind, Axel H. (Journal of Banking & Finance, 2006)
We use an affine asset pricing model to jointly value stocks and bonds. This enables us to derive endogenous correlations and to explain how economic fundamentals influence the correlation between stock and bond returns. The presented model is implemented for G7 post-war economies and its in-sample and out-of-sample performance is assessed by comparing the correlations generated by the model with conventional statistical measures. The affine framework developed in this paper is found to generate stock–bond correlations that are in line with empirically observed figures.